Posthumanist Feminism and Interspecies Affect in Nalo Hopkinson’s Midnight Robber - Martín-Lucas, Belén (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
This paper examines the posthuman affective communities in Nalo Hopkinson’s dystopia Midnight Robber (2000), from an intersectional approach. It focuses on the interspecies affinity developed between a cyborg Black girl and other posthuman beings in outer space, where subaltern ‘artisans,’ machines, and indigenous communities provide nurturing affects of love and compassion that engender mutual respect and solidarity.